Nitric oxide-cGMP-PKG signaling in the bed nucleus of the stria terminalis modulates the cardiovascular responses to stress in male rats - Barretto-de-Souza, Lucas [UNESP]; Adami, Mariane B. [UNESP]; Oliveira, Leandro A. [UNESP]; Gomes-de-Souza, Lucas [UNESP]; Duarte, Josiane O. [UNESP]; Almeida, Jeferson [UNESP]; Crestani, Carlos C. [UNESP] (Elsevier, 2018)
The bed nucleus of the stria terminalis (BNST) constitutes an important component of neural substrates of physiological and behavioral responses to aversive stimuli, and it has been implicated on cardiovascular responses evoked by stress. Nevertheless, the local neurochemical mechanisms involved in BNST control of cardiovascular responses during aversive threats are still poorly understood. Thus, the aim of the present study was to assess the involvement of activation in the BNST of the neuronal isoform of the enzyme nitric oxide synthase (nNOS), as well as of signaling mechanisms related to nitric oxide effects such as soluble guanylate cyclase (sGC) and protein kinase G (PKG) on cardiovascular responses induced by an acute session of restraint stress in male rats. We observed that bilateral microinjection of either the nonselective NOS inhibitor Nω-Nitro-L-arginine methyl ester (L-NAME), the selective nNOS inhibitor Nω-Propyl-L-arginine (NPLA) or the sGC inhibitor 1H-[1,2,4]Oxadiazolo[4,3-a]quinoxalin-1-one (ODQ) into the BNST enhanced the tachycardic response and decreased the drop in tail cutaneous temperature evoked by acute restraint stress, but without affecting the increase on blood pressure. Bilateral BNST treatment with the selective PKG inhibitor KT5823 also facilitated the heart rate increase and decreased the drop in cutaneous temperature, in addition to enhancing the blood pressure increase. Taken together, these results provide evidence that NO released from nNOS and activation of sGC and PKG within the BNST play an inhibitory influence on tachycardia to stress, whereas this signaling mechanism mediates the sympathetic-mediated cutaneous vasoconstriction.
Keywords: Blood pressure; BNST; Guanylate cyclase; Heart rate; Stress; Sympathetic